INDONESIA’S EFFORT TO MEET WHO RECOMMENDATION ON EXCLUSIVE BREASTFEEDING 2012-2023 - Nabilah, Fazah Amalia; Trisnaningtyas, Januari Pratama Nurratri (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: The World Health Organization (WHO) provides policy recommendations related to exclusive breastfeeding that can be adopted by UN member states. In Indonesia, the government has issued a policy to support exclusive breastfeeding based on WHO recommendations. Objectives: To describe effort in exclusive breastfeeding governance in Indonesia from 2012 to 2023 according to WHO recommendations. Method: This research uses a descriptive qualitative methodology and relies on a literature review from a variety of sources, including books, journals, articles, websites, and more, to gather information about Indonesia's efforts to meet the WHO recommendations about exclusive breastfeeding from 2012 to 2023. Results: It showed that there were efforts in the community due to applied policies, such as the provision of lactation rooms in public facilities, the formation of Breastfeeding Support Groups, the training of breastfeeding counselors, and the establishment of the PelanggaranKode website to continue to support the exclusive breastfeeding program. Conclusion: There are efforts indicating that government policies are not yet optimal. Recommendations for future research should be more specific by exploring strategies for effective advocacy and policy change to support breastfeeding, as well as evaluating the impact of global health initiatives and programs that promote breastfeeding